Analisis Pengaruh Perencanaan Pembangunan Terhadap Perkembangan Aktivitas Masyarakat di Desa Sinasih - Demak Purba; Dian G Purba; Dina Revani Saragih; Endang Silalahi; Grace Naibaho; Jelita Simbolon; Mei Meri C Damanik; Tia Amanda Saragih; Widiya Damanik; Yuri Varanti (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the extent of development of community activities after infrastructure development, especially in the construction of road infrastructure in the Sinasih Village area, Silau Kahean District, Simalungun Regency, as well as aspects related to community participation in village infrastructure development. The approach taken in this research is a qualitative approach that uses informant analysis units with data collection techniques through in-depth interviews and document studies. The analysis used is qualitative descriptive analysis. The research results show that: first, the village road infrastructure that has been built step by step has had a significant influence on improving the welfare of the community, especially the community in the Sinasih Village area. Second, aspects related to community activities, namely the type of work and level of education, also influence the rate of increase in community welfare itself.